Turnbull-Cutait technique without ileostomy after total mesorectal excision is associated with acceptably low early post-operative morbidity - Guner, Osman Serhat; Tumay, Latif Volkan (WILEY, 2021)
Background: This study aimed to compare the standard one-stage coloanal anastomosis (CAA) technique plus diverting ileostomy and the Turnbull-Cutait (T-C) technique with delayed CAA in terms of early post-operative morbidity in patients with low rectal cancer. Methods: A total of 33 patients with non-metastatic distal rectal cancer who were operated with one of the two different reconstruction methods (one-stage CAA plus diverting ileostomy or two-stage T-C technique with delayed CAA) after total mesorectal excision were included in this retrospective study. The two groups were compared for early postoperative morbidity within 30 post-operative days using complication frequency, Clavien-Dindo classification and Comprehensive Complication Index scores. Results: The two groups did not differ in terms of morbidity parameters, including frequency of any morbidity, presence of grade 3b morbidity requiring management under general anaesthesia, as well as Comprehensive Complication Index score (P > 0.05 for all). Conclusion: Our findings suggest that the two techniques did not differ in terms of early post-operative morbidity. Owing to its comparable morbidity and safety to CAA plus concomitant ileostomy performed at the same session, the T-C technique may be considered in distal rectal cancer patients refusing to have a temporary stoma and in patients in whom CAA poses technical difficulties during the initial operation.
Keywords: coloanal anastomosis; early post-operative morbidity; ileostomy; rectal cancer; total mesorectal excision; Turnbull-Cutait technique